Publisher Correction: Survival analysis of Rural Clinical School of Western Australia graduates: the long-term work of building a long-term rural medical workforce - Surabhi Gupta; Hanh Ngo; Tessa Burkitt; Ian Puddey; Denese Playford (BMC, 2020)
In the original publication of this article [1], an error occurred during the publication of this article in Table 2.